2017
DOI: 10.1186/s13018-017-0554-7
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic characteristics of serial casting on congenital scoliosis: a comparison with non-congenital cases from a single-center experience

Abstract: BackgroundThe therapeutic efficacy of serial casting on idiopathic scoliosis has been gradually documented. However, literatures on serial casting for congenital scoliosis (CS) remain extremely rare. This paper aimed to compare the treatment outcomes of serial casting between CS and non-CS patients to comprehensively evaluate the therapeutic characteristics of serial casting on CS patients.MethodsA total of 23 early-onset scoliosis cases were included and divided into congenital scoliosis (CS, n = 8) and non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…Controlling for curve severity reduced I 2 but was not associated with the mean difference in Cobb angle from before to after casting in this review. The bubble plot with the meta-regression line showed an inverse 11 Three patients had skin irritation, one increased lumbar lordosis requiring remoulding of the cast and one patient had early satiety improved with an abdominal window Baulesh et al 12 Two patients had respiratory complications leading to a break from casting and one had superficial skin irritation Fletcher et al 18 Three patients with skin irritations, one cast removal for vomiting and one epileptic patient had increased frequency of seizure requiring removal of the cast a Waldron et al 19 Two patients had skin irritation, and in two patients, casting was stopped due to intolerance of the patient or the family a Abraham et al 20 Five tight casts were trimmed and one soiled cast was removed Iorio et al 21 No major complications Cao et al 22 Two patients had ulcers requiring local skin care Hassanzadeh et al 23 10 skin irritations, three patients had reactive airway disease requiring overnight stay, two cases of nausea, two cases progressed despite casting and one case of noncompliance Gomez et al 24 No major complications Stasikelis et al 25 No major complications Welborn et al 26 One pulmonary complication resulted in cast discontinuation relationship between age at the first cast and Cobb angle correction immediately after casting (Figure 3). Moreover, the drawn funnel plot was asymmetrical, and the cylindrical contour is suggestive of a large heterogeneity between studies rather than reporting bias (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Controlling for curve severity reduced I 2 but was not associated with the mean difference in Cobb angle from before to after casting in this review. The bubble plot with the meta-regression line showed an inverse 11 Three patients had skin irritation, one increased lumbar lordosis requiring remoulding of the cast and one patient had early satiety improved with an abdominal window Baulesh et al 12 Two patients had respiratory complications leading to a break from casting and one had superficial skin irritation Fletcher et al 18 Three patients with skin irritations, one cast removal for vomiting and one epileptic patient had increased frequency of seizure requiring removal of the cast a Waldron et al 19 Two patients had skin irritation, and in two patients, casting was stopped due to intolerance of the patient or the family a Abraham et al 20 Five tight casts were trimmed and one soiled cast was removed Iorio et al 21 No major complications Cao et al 22 Two patients had ulcers requiring local skin care Hassanzadeh et al 23 10 skin irritations, three patients had reactive airway disease requiring overnight stay, two cases of nausea, two cases progressed despite casting and one case of noncompliance Gomez et al 24 No major complications Stasikelis et al 25 No major complications Welborn et al 26 One pulmonary complication resulted in cast discontinuation relationship between age at the first cast and Cobb angle correction immediately after casting (Figure 3). Moreover, the drawn funnel plot was asymmetrical, and the cylindrical contour is suggestive of a large heterogeneity between studies rather than reporting bias (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“… 6 , 10 Hemivertebrectomy or in situ fusion is the common treatment for patients with a short angular congenital deformity. Recent reports of cast treatment for long congenital curves with multiple anomalous vertebrae found thoracic growth rate was slower than normal, 11 but that T1-T12 height increased significantly over treatment. 12 Neuromuscular patients often have respiratory and gastrointestinal co-morbidities, 9 but their cast treatment outcomes have been described.…”
Section: Discussionmentioning
confidence: 97%
“…Progressive CS in the immature spine poses unique management challenges for the surgeons with limited intervention modalities available. Several treatment options exist to correct deformity or prevent progression, including casting, in situ fusion, growing rods, and vertical expandable prosthetic titanium rib [1013]. In earlier literatures concerning treatment of patients with CS, the choice of age at surgery was still in debate [1416].…”
Section: Introductionmentioning
confidence: 99%
“…Conservative techniques are conventionally considered inappropriate for patients with CS due to the progressive spinal deformity. Nevertheless, taking advantage of delay of the initial surgery, recently serial casting has been applied to the treatment of CS [10, 11]. Demirkiran et al [11] reviewed a total of 11 CS patients treated with serial cast application and reported that it is a safe and effective time-buying strategy to delay the surgical interventions in congenital deformities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation